Offerings a Reflection of God in the Tradition of the Bonokeling Community in Banyumas Regency, Indonesia - Rohman, Abdul; Suhardi, Imam; Noviko, Sendy; Huda, Ulul; Yamin, Muhammad (Journal of Ecohumanism, 2024)
The purpose of this research are to find out the position of offerings in the Bonokeling community which they do regularly at a predetermined time. This research method uses qualitative descriptive with ethnographic type. Data were collected through observation and interview. Data analysis used interactive method. The result of the research found: 1) The offerings carried out by the Bonokeling community are a reflection of offerings to God and the spirits of their ancestors who are believed to realize safety, peace and prosperity; 2) The dish as an offering to God is an offering that has existed since the time of the prophet Adam, as well as the sacrifice performed by his two sons named Qabil and Habil; 3) God, who is embodied in the ritual of offerings, is included in the realm of the supernatural, the consequence is that human sacrifice and devotion are not offerings in material form, but respect through behavior and inner attitude reflected in the form of intention and sincerity as a taqwa (manifestation of obedience to God). Therefore, offerings buried for ancestral spirits are behaviors and attitudes that are not under the realm of the supernatural, because spirits in the supernatural realm do not require material offerings, except for human behavior and inner attitudes towards them, such as prayer